Engineering of a novel subnanomolar affinity fibronectin III domain binder targeting human programmed death-ligand 1. Issue 5 (15th October 2019) - Ramakrishnan, Sindhuja; Natarajan, Arutselvan; Chan, Carmel T; Panesar, Paramjyot Singh; Gambhir, Sanjiv S
Abstract: The programmed death-ligand 1 (PD-L1) is a major checkpoint protein that helps cancer cells evade the immune system. A non-invasive imaging agent with rapid clearance rate would be an ideal tool to predict and monitor the efficacy of anti-PD-L1 therapy. The aim of this research was to engineer a subnanomolar, high-affinity fibronectin type 3 domain (FN3)-based small binder targeted against human PD-L1 (hPD-L1) present on tumor cells. A naive yeast G4 library containing the FN3 gene with three binding loop sequences was used to isolate high-affinity binders targeted to purified full-length hPD-L1. The selected binder clones displayed several mutations in the loop regions of the FN3 domain. One unique clone (FN3hPD-L1-01 ) with a 6x His-tag at the C-terminus had a protein yield of >5 mg/L and a protein mass of 12 kDa. In vitro binding assays on six different human cancer cell lines (MDA-MB-231, DLD1, U87, 293 T, Raji and Jurkat) and murine CT26 colon carcinoma cells stably expressing hPD-L1 showed that CT26/hPD-L1 cells had the highest expression of hPD-L1 in both basal and IFN-γ-induced states, with a binding affinity of 2.38 ± 0.26 nM for FN3hPD-L1-01 . The binding ability of FN3hPD-L1-01 was further confirmed by immunofluorescence staining on ex vivo CT26/hPD-L1 tumors sections. The FN3hPD-L1-01 binder represents a novel, small, high-affinity binder for imaging hPD-L1 expression on tumor cells and would aid in earlier imaging of tumors. Future clinical validation studies of the labeled FN3hPD-L1 binder(s) have the potential to monitor immune checkpoint inhibitors therapy and predict responders.